Evaluation of conservative management in uncomplicated acute appendicitis - M., Vignesh; Chejara, Rajkumar; Arya, S. V; Bhatia, Ankit; Chaudhary, Rohit; Raj, Monish (International Journal of Research in Medical Sciences, 2021)
Background: Appendectomy has been the treatment for acute appendicitis for years based on the understanding that acute appendicitis always leads to perforation and peritonitis. However, there is growing evidence that a significant proportion of patients can be successfully managed with conservative treatment without developing gangrene or perforation. Conservative treatment avoids discomfort, surgery-related morbidities and minimizes treatment cost. Methods: 60 patients taken up for conservative management were evaluated and followed up for 6 months. Study patients received intravenous antibiotics for 2 days. Repeated clinical and TLC monitoring were done. In patients whose clinical condition did not improve, appendectomy was performed. Follow-up at 10 days, 30 days, 3 months and 6 months were carried out to assess recurrence in conservatively managed patients. Results: In this study, the mean age was 25.65 years with a standard deviation of ±8.96 years. The incidence of uncomplicated appendicitis was 63.3% in males and 36.7% in females. Mean Alvarado score was 7.75 with a standard deviation of ±1.20. Failure of conservative management (conversion to appendectomy) was observed in 11.7% of patients and 4 patients (6.6%) had recurrence within 6 months. The overall treatment efficacy was 81.7%. Conclusions: In many cases, first attack of uncomplicated acute appendicitis can be treated successfully by conservative management. Treatment failure on primary admission as well as short-term recurrence up to six months after conservative treatment is low and acceptable. Incidence of complications like perforation and abscess formation are also statistically low.